Genetic Architecture of Stroke of Undetermined Source: Overlap with Known Stroke Etiologies and Associations with Modifiable Risk Factors. Issue 5 (3rd March 2022) - Georgakis, Marios K.; Parodi, Livia; Frerich, Simon; Mayerhofer, Ernst; Tsivgoulis, Georgios; Pirruccello, James P.; Slowik, Agnieszka; Rundek, Tatjana; Malik, Rainer; Dichgans, Martin; Rosand, Jonathan; Anderson, Christopher D.; et al.
Abstract : Objective: Ischemic stroke etiology remains undetermined in 30% of cases. We explored the genetic architecture of stroke classified as undetermined to test if mechanisms and risk factors underlying large‐artery atherosclerotic (LAAS), cardioembolic (CES), and small‐vessel stroke (SVS) contribute to its pathogenesis. Methods: We analyzed genome‐wide data from 16, 851 ischemic stroke cases and 32, 473 controls. Using polygenic risk scores for LAAS, CES, and SVS, we assessed the genetic overlap with stroke of undetermined source and used pairwise genomewide association study (GWAS‐PW) to search for shared loci. We then applied Mendelian randomization (MR) to identify potentially causal risk factors of stroke of undetermined source. Results: Genetic risk for LAS, CES, and SVS was associated with stroke of undetermined source pointing to overlap in their genetic architecture. Pairwise analyses revealed 19 shared loci with LAAS, 2 with CES, and 5 with SVS that have been implicated in atherosclerosis‐related phenotypes. Genetic liability to both carotid atherosclerosis and atrial fibrillation was associated with stroke of undetermined source, but the association with atrial fibrillation was attenuated after excluding cases with incomplete diagnostic workup. MR analyses showed effects of genetically determinants of blood pressure, diabetes, waist‐to‐hip ratio, inflammatory pathways (IL‐6 signaling, MCP‐1/CCL2 levels), and factor XI levels on stroke of undetermined source. Interpretation: Stroke of undetermined source shares genetic and vascular risk factors with other stroke subtypes, especially LAAS, thus highlighting the diagnostic limitations of current subtyping approaches. The potentially causal associations with carotid atherosclerosis and atherosclerotic risk factors might have implications for prevention strategies targeting these mechanisms. ANN NEUROL 2022;91:640–651